2020
DOI: 10.1177/2150135120941461
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Follow-Up of Pericardium for the Ventricular Component in Atrioventricular Septal Defect Repair

Abstract: Background: Despite the improved outcome in complete atrioventricular septal defect (AVSD) repair, reoperations for left atrioventricular valve (LAVV) dysfunction are common. The aim of this study was to evaluate the effect of fresh untreated autologous pericardium for ventricular septal defect (VSD) closure on atrioventricular valve function and compare the results with the use of treated bovine pericardial patch material. Methods: Clinical and echocardiographic data were collected of patients with complete A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Fresh autologous pericardium was found to be durable without evidence of late patch calcification, stiffness, or aneurysmal degeneration and can be an excellent alternative patch material for repair. 13,14 Mid-and long-term follow-up have been encouraging as gradients remained low and no reinterventions were needed.…”
Section: Discussionmentioning
confidence: 97%
“…Fresh autologous pericardium was found to be durable without evidence of late patch calcification, stiffness, or aneurysmal degeneration and can be an excellent alternative patch material for repair. 13,14 Mid-and long-term follow-up have been encouraging as gradients remained low and no reinterventions were needed.…”
Section: Discussionmentioning
confidence: 97%
“…In recent years, several studies have reported clinical outcomes of septal repair with autologous pericardium patch. In 2020 IJsselhof et al reported that ventricular septal defects can safely be closed with either untreated autologous pericardium or xeno-pericardium, with no difference in left atrio-ventricular valve regurgitation or need for reoperation; the study was conducted on 77 paediatric patients (median age 3.6 months) and the median follow-up was 17.5 years (IJsselhof et al 2020 ). A retrospective study on 156 patients with a median follow-up of 37 months have demonstrated that autologous pericardium treated with glutaraldehyde is as effective as Dacron mesh in ventricular septal defects repair, with no differences in clinical outcomes and reinterventions (Desai et al 2022 ).…”
Section: Discussionmentioning
confidence: 99%